PERAN PERS DALAM PENINGKATAN DAYA SAING DAERAH - Wicaksono, Kukrit Suryo (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2015)
AbstractNewspaper is not only depend on the factors of production, but also outside factors ofproduction are called off-print. One such factor is the newspaper’s role as a